2014
DOI: 10.1007/s00702-014-1343-7
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-L-carnitine and oxaloacetate in post-treatment against LTP impairment in a rat ischemia model. An in vitro electrophysiological study

Abstract: A high proportion of research relating to cerebral ischemia focuses on neuroprotection. The application of compounds normally present in the organism is popular, because they do not greatly influence the synaptic activity by receptor modulation, and can be administered without serious side effects. Oxaloacetate (OxAc) and acetyl-L-carnitine (ALC) are such favorable endogenous molecules. ALC can exert a protective effect by improving the energy state of the neurons under ischemic conditions. A promising neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The preparation and maintenance of rat hippocampal slices were described previously (Kocsis et al, 2014;Kocsis et al, 2015). Briefly, the animals were decapitated and the middle parts of the hippocampi were placed in ice-cold artificial cerebrospinal fluid (aCSF) composed of (in mM): 130 NaCl, 3.5 KCl, 1 NaH 2 PO 4 , 24 NaHCO 3 , 1 CaCl 2 , 3 MgSO 4 and 10 D-glucose (all from Sigma, Germany), saturated with 95% O 2 + 5% CO 2 .…”
Section: In Vitro Slice Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation and maintenance of rat hippocampal slices were described previously (Kocsis et al, 2014;Kocsis et al, 2015). Briefly, the animals were decapitated and the middle parts of the hippocampi were placed in ice-cold artificial cerebrospinal fluid (aCSF) composed of (in mM): 130 NaCl, 3.5 KCl, 1 NaH 2 PO 4 , 24 NaHCO 3 , 1 CaCl 2 , 3 MgSO 4 and 10 D-glucose (all from Sigma, Germany), saturated with 95% O 2 + 5% CO 2 .…”
Section: In Vitro Slice Preparationmentioning
confidence: 99%
“…ALC is actively transported across the bloodbrain barrier to the brain (Burlina et al 1989), where it has a relative high concentration (Shug et al 1982). Several studies have demonstrated the neuroprotective effect of ALC against different neurodegenerative diseases, such as Alzheimer's disease, ischemia or neuropathic 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 investigated the neuroprotective effect of ALC against global hypoperfusion in a 2-vessel occlusion (2VO) model (Kocsis et al 2014, Kocsis et al 2015. The effects of ALC were also tested on striatal slices in an in vitro ischemia model, where it prevented the loss of the recorded field excitatory postynaptic potentials (fEPSPs) through the activation of M2 muscarinic receptors and the choline uptake system (Picconi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…All these derivatives can transport therapeutic compounds through the BBB [161]. Over the past 5 years, the interest in the therapeutic potential of l-carnitine and acetyll-carnitine (ALCAR) for the transport of compounds across the BBB and for neuroprotection has significantly increased [162][163][164][165][166][167].…”
Section: L-carnitinementioning
confidence: 99%